90PHigh MICB expression confers prognostic benefit in colorectal cancer. (24th November 2019) - Yu, S
Abstract: Background: Immune surveillance is closely related to MHC and its associated molecules. The MHC class I chain related B molecule (MICB) is one of the ligands of NKG2D receptor. NKG2D receptor exists in NK cells and CD8+ T cells, which mediate anti-tumor response and immune surveillance. MICB is expressed by intestinal epithelium and epithelial tumors as well. Cancer cells express MICB as the consequence of cellular stress. But tumor cells might develop evasive pathways to avoid NK cell attack. Shedding is a way for cancer cells to remove or avoid the surface expression of MICB. Previous studies haven't clearly figured out the prognostic value of MICB in colorectal cancer (CRC). Here, we figured out the relationship between MICB and prognosis in a CRC cohort of Zhongshan Hospital. The prognostic benefit was also validated in GSE39582 from Gene Expression Omnibus repository. Methods: 863 consecutive CRC patients from 2008 to 2012 without prior treatment were enrolled. 556 CRC patients between 1987 to 2007 were collected from GSE39582. MICB was detected by immunochemistry. MICB score equaled MICB intensity multiplied by the percentage of positive cells among all tumor cells. The cut-off value of MICB score was calculated by X-tile. The association between clinicopathological features and MICB were accessed by chi-square test. Kaplan-Meier analysis and log-rank test were performed to evaluate the relationship between MICB and overall survival. Univariate and multivariate cox regression analyses were performed to identify the independent prognostic factors. Results: High MICB was significantly associated with non-mucinous histological type (p < 0.001) and ≤4.0cm tumor size (p = 0.001). Kaplan-Meier analyses and log-rank test showed high MICB group had a better overall survival (p = 0.002). In cox regression analyses of Zhongshan cohort, MICB was confirmed as an independent prognostic factor of OS (p = 0.008, HR = 0.741, 95% CI = 0.594-0.924). Conclusions: MICB was identified as a new independent prognostic factor in stage one to stage four CRC patients. CRC with high MICB expression conferred survival benefit. Legal entity responsible for the study: Zhongshan Hospital, Fudan University, Shanghai, China. Funding: Has not received any funding. Disclosure: The author has declared no conflicts of interest.